Realization of room temperature lithium metal battery with high Li+ conductive lithium garnet solid electrolyte. Issue 17 (1st December 2019) - Indu, M.S.; Alexander, George V.; Deviannapoorani, C.; Murugan, Ramaswamy
Abstract: Garnet structured solid electrolytes are suitable candidates for lithium metal batteries due to their high lithium ion conductivity and good electrochemical stability. However, large electrode-electrolyte interface resistance still remains a major challenge. Here, we demonstrate realization of room temperature quasi-solid-state battery with high lithium ion conducting Li6.5 La3 Zr1.75 Te0.25 O12 (Te-LLZ) as solid electrolyte. To overcome the high interface resistance, we have used gold (Au) interlayer between lithium metal and Te-LLZ. By introducing Au buffer layer, we observed a significant reduction in the interface resistance from 1868 Ω cm 2 to 30 Ω cm 2 with a stable lithium stripping/platting profile, suggesting a homogeneous lithium ion transport at the lithium/Te-LLZ interface. A quasi-solid-state battery with lithium metal as anode, lithium cobalt oxide (LiCoO2 ) as cathode and surface engineered Te-LLZ electrolyte with polypropylene (PP) interlayer on the cathode side was demonstrated. The fabricated quasi-solid-state battery delivered an initial discharge capacity of 137 mA h g -1 (50 μA cm -2 ) and 132 mA h g -1 (150 μA cm -2 ) at room temperature (25 °C) and 60 °C, respectively.